2020
DOI: 10.3390/ijerph17041456
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the External Loads Encountered during Competition between Elite, Junior Male and Female Basketball Players

Abstract: The aim of the present study was to compare external loads (EL) between elite, junior, male and female basketball players. Male (n = 25) and female players (n = 48) were monitored during 11 competitive matches (3 matches per team). EL was measured using local positioning system and microsensor technology to determine total, high-intensity (14–21 km·h−1), and sprint (>21 km·h−1) distance (m) covered, total (n) and relative (n·min−1) accelerations and decelerations, ratio of accelerations:decelerations, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(46 citation statements)
references
References 41 publications
3
42
1
Order By: Relevance
“…Although multiple investigations have measured the PL and PL/min during official games and games-based drills in basketball (Schelling and Torres, 2016 ; Fox et al, 2018 ; Vázquez-Guerrero et al, 2018 , 2019a , b ; Pino-Ortega et al, 2019 ; Conte et al, 2020 ; Fernández-Leo et al, 2020 ; García et al, 2020 ; O'Grady et al, 2020 ; Portes et al, 2020 ; Ransdell et al, 2020 ), no study has assessed the external load imposed during single basketball-specific activities measured via TMA. To the best of our knowledge, a similar approach was previously used only in netball, with two official games analyzed via TMA and IMUs, revealing that on average the highest PL was registered during off-ball guarding actions (Bailey et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Although multiple investigations have measured the PL and PL/min during official games and games-based drills in basketball (Schelling and Torres, 2016 ; Fox et al, 2018 ; Vázquez-Guerrero et al, 2018 , 2019a , b ; Pino-Ortega et al, 2019 ; Conte et al, 2020 ; Fernández-Leo et al, 2020 ; García et al, 2020 ; O'Grady et al, 2020 ; Portes et al, 2020 ; Ransdell et al, 2020 ), no study has assessed the external load imposed during single basketball-specific activities measured via TMA. To the best of our knowledge, a similar approach was previously used only in netball, with two official games analyzed via TMA and IMUs, revealing that on average the highest PL was registered during off-ball guarding actions (Bailey et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The index takes into account the instantaneous rate of change of acceleration and divides it by a scaling factor of 100 (Nicolella et al, 2018 ). The reliability of PL (within-device CV = 0.91–1.05%, between-device CV = 1.02–1.90%) has been previously assessed (Boyd et al, 2011 ) and this metric has been widely used in basketball (Schelling and Torres, 2016 ; Fox et al, 2017 , 2018 ; Pino-Ortega et al, 2019 ; Vázquez-Guerrero et al, 2019a , b ; Conte et al, 2020 ; García et al, 2020 ; Lukonaitienė et al, 2020 ; Portes et al, 2020 ; Ransdell et al, 2020 ; Russell et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is unclear if or how selection is influenced by the sex and age of athletes in a SPP. In this regard, basketball research has identified differences in match demands between sex [9,10] and age groups [11]. In turn, these variations in match demands between cohorts are likely underpinned by differences in anthropometric and physical attributes between sexes and age groups.…”
Section: Introductionmentioning
confidence: 99%